Antibacterial Activity of Legundi Leaf (Vitex trifolia) Essential Oil Using In-Vitro and In-Silico Methods - Retno Indriatie; Warsito Warsito; Masruri Masruri (The Journal of Pure and Applied Chemistry Research, 2023)
Staphylococcus aureus causes many severe diseases, such as meningitis, lung infection, and hematogenous osteomyelitis. The prolonged use of antibiotic drugs leads to antimicrobial resistance (AMR), decreasing their effectiveness against S. aureus. Therefore, novel drugs isolated from natural products have been the focus of many researchers to solve that problem. The essential oils isolated from Vitex trifolia leaf have many pharmacological activities, including antibacterial and antifungal activities. In this research, essential oil was isolated by distillation, followed by GC-MS analysis. The antibacterial activity of the essential oil was conducted using a disk diffusion test (Kirby-Bauer) and by molecular docking study. The essential oil yield from distillation was 0.13%, containing major compounds such as sabinene, eucalyptol, terpinen-4-ol, α-terpineol, limonene, and caryophyllene. The essential oil gave intermediate inhibition against S. aureus with a 6.91 ± 0.03 mm inhibition zone in 20 mg/mL of the sample. Using molecular docking study, caryophyllene and α-terpineol were the key compounds for inhibiting the active site of tyrosyl-tRNA synthetase, sortase A, and dihydrofolate reductase that are responsible for the S. aureus growth and development.